1988
DOI: 10.1002/eji.1830181018
|View full text |Cite
|
Sign up to set email alerts
|

Interferon‐γ and tumor necrosis factor induce the L‐arginine‐dependent cytotoxic effector mechanism in murine macrophages*

Abstract: We tested several monokines and muramyl dipeptide (MDP) to determine whether they induce the L-arginine-dependent effector mechanism in cultured murine macrophages. Recombinant interferon-gamma (rIFN-gamma) and recombinant tumor necrosis factor (rTNF) synergize to induce nitrite (NO2-) and nitrate (NO3-) synthesis from L-arginine as well as to cause inhibition of the iron-dependent enzyme aconitase in macrophages. Unlike rTNF, recombinant interleukin 1 (rIL 1) and rIL 6/B cell stimulatory factor 2 (rIL 6/BSF-2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
264
0
9

Year Published

1992
1992
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 512 publications
(283 citation statements)
references
References 26 publications
10
264
0
9
Order By: Relevance
“…We also demonstrate that IFN-y, but not TNF-a, is an important mediator of the BCG-induced nonspecific host resistance against syngeneic ovarian tumor cells in vivo. This observation is contrary to in vitro studies in which IFN-y was thought to be important for the priming of macrophages and TNF-a was thought to be necessary for full induction of activated macrophage cytotoxicity (8,9). Furthermore, others (14) showed that neutralization of either IFN--y or TNF-a blocked the BCG-induced in vivo synthesis of nitrogen oxides from L-arginine as well as the protection against Francisella tularensis.…”
Section: Methodsmentioning
confidence: 69%
See 1 more Smart Citation
“…We also demonstrate that IFN-y, but not TNF-a, is an important mediator of the BCG-induced nonspecific host resistance against syngeneic ovarian tumor cells in vivo. This observation is contrary to in vitro studies in which IFN-y was thought to be important for the priming of macrophages and TNF-a was thought to be necessary for full induction of activated macrophage cytotoxicity (8,9). Furthermore, others (14) showed that neutralization of either IFN--y or TNF-a blocked the BCG-induced in vivo synthesis of nitrogen oxides from L-arginine as well as the protection against Francisella tularensis.…”
Section: Methodsmentioning
confidence: 69%
“…NO produced by the activated macrophages is responsible for this cytostatic and/or cytolytic activity (1)(2)(3). Interferon 'y (IFN-y) is important for the priming of macrophages, and tumor necrosis factor a (TNF-a) or some other cytokine or bacterial lipopolysaccharide (LPS) is necessary for full induction of activated macrophage cytotoxicity (6)(7)(8)(9). However, the role of NO in mediating tumoricidal activity in vivo is not known.…”
mentioning
confidence: 99%
“…Like LPS, TNF also induces the calcium-independent isoform of NOS in vitro (Drapier et al, 1988;Kilbourn & Belloni, 1990). Systemic administration of TNF increases NO production (Kosaka et al, 1992) and causes NO-mediated vasodilatation and vascular hyporeactivity to vasoconstrictors in vivo (Vicaut & Baundry, 1992) and ex vivo (Takahashi et al, 1992;Foulkes & Shaw, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…It has improved antitumour activity and 12-fold higher dose potency when compared to FAA, and is a candidate drug for clinical trial. FAA and 5,6-MeXAA share many properties with endotoxin: they induce the synthesis of tumour necrosis factor (TNF) (North & Havell, 1988;Mace et al, 1990) and stimulate the formation of nitric oxide, both in vitro (Drapier et al, 1988;Thomsen et al, 1990) and in vivo (Stuehr & Marletta, 1985;Thomsen et al, 1991). There are two main facets to the action of these agents.…”
mentioning
confidence: 99%